2007
DOI: 10.1542/peds.2006-2122
|View full text |Cite
|
Sign up to set email alerts
|

Legal and Ethical Considerations: Risks and Benefits of Postpartum Depression Screening at Well-Child Visits

Abstract: Pediatric professionals are being asked to provide an increasing array of services during well-child visits, including screening for psychosocial and family issues that may directly or indirectly affect their pediatric patients. One such service is routine screening for postpartum depression at pediatric visits. Postpartum depression is an example of a parental condition that can have serious negative effects for the child. Because it is a maternal condition, it raises a host of ethical and legal questions abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 43 publications
1
50
0
3
Order By: Relevance
“…In their article about the legal and ethical considerations of postpartum depression screening at well-child visits, Chaudron et al concluded: "We believe that from the perspective of feasibility, and now from the legal and ethical standpoints, the benefits of screening outweigh the risks." 39 The primary care provider (PCP) has a particularly important role in the early identification of maternal depression and facilitation of intervention to prevent adverse outcomes for the infant, the mother, and the family. The PCP may be the first clinician to see the infant and mother after the infant is born; therefore, the PCP has very early access.…”
Section: The Role Of the Primary Care Providermentioning
confidence: 99%
“…In their article about the legal and ethical considerations of postpartum depression screening at well-child visits, Chaudron et al concluded: "We believe that from the perspective of feasibility, and now from the legal and ethical standpoints, the benefits of screening outweigh the risks." 39 The primary care provider (PCP) has a particularly important role in the early identification of maternal depression and facilitation of intervention to prevent adverse outcomes for the infant, the mother, and the family. The PCP may be the first clinician to see the infant and mother after the infant is born; therefore, the PCP has very early access.…”
Section: The Role Of the Primary Care Providermentioning
confidence: 99%
“…This extension of practice to a nonpatient population may create an ethical challenge for pediatric providers, although they are often prompted by their physician colleagues to take stronger and more active roles in screening and referral as an extension of their care and advocacy for infants and young children. [19][20][21] The present study is grounded within this growing evidence base informing public health approaches to perinatal depression screening and intervention by healthcare providers. Rigorous program evaluation emphasizes the importance of selecting intervention approaches that measure both the process of change (often referred to as ''program theory'') and the outcomes of a program or service.…”
Section: Journal Of Women's Healthmentioning
confidence: 99%
“…In New Zealand, women are not formally screened for depression, although the Well Child Schedule currently recommends use of the EPDS at core child health contacts at 6 weeks, 3 months and 5 months [25]. In the USA and Australia, similar recommendations have been made [17,26]. These timings appear to coincide with routine service contacts rather than an evidence base to support optimal screening outcomes, which will encourage pragmatic use of screening in practice and identify some women at risk, but may not be the most appropriate times to ensure as many women as possible are identified.…”
Section: Timing Of Screeningmentioning
confidence: 99%